Striatal functional connectivity in chronic ketamine users: a pilot study. (2nd January 2020) - Hung, Chia-Chun; Zhang, Sheng; Chen, Chun-Ming; Duann, Jeng-Ren; Lin, Ching-Po; Lee, Tony Szu-Hsien; Li, Chiang-Shan R.
ABSTRACT: Background : The striatum supports motivated behavior and impulse control. Altered striatal activation and connectivity has been observed in link with impulse control dysfunction in individuals with drug addiction. Objectives : We examined how resting state functional connectivity (rsFC) of the striatum is altered as a result of chronic ketamine misuse. Methods : Thirty-six ketamine users (10 women) and 20 healthy controls (9 women) completed an assessment with the Barratt Impulsiveness Scale (BIS-11) and magnetic resonance imaging. In SPM we examined voxel-wise connectivities of the caudate, pallidum, putamen, and ventral striatum in ketamine users (versus healthy controls) and in association with BIS-11 score and duration of use, all at a corrected threshold. Results : Compared to controls, ketamine users showed higher connectivity between caudate and dorsal anterior cingulate cortex and between pallidum and bilateral cerebellum. In ketamine users, putamen showed higher connectivity with the left orbitofrontal cortex (OFC) in association with both BIS-11 score and months of ketamine use. Mediation analyses suggest that the connectivity z score mediated the relationship between impulsivity and duration of use. Conclusions : These preliminary findings highlighted altered striatal connectivity in chronic ketamine users, and the potential role of putamen OFC connectivity in supporting the correlation between impulsivity and duration of ketamine use. If replicated in a larger sample, these findings may represent neural markers of ketamine misuse.